Eine Frage der Perspektive? Die Wahrnehmung von Steuern bei Anlageentscheidungen zur privaten Altersvorsorge - Corinna Treisch; Silvia Jordan (Arbeitskreis Quantitative Steuerlehre (arqus), 2008)
This study empirically analyses the influence of tax concessions on decisions regarding retirement savings in Austria. We analyse real decisions on retirement savings by using qualitative data. This allows us to examine how different, perceived decision-making criteria have led to actual investment decisions by taking into account the context in which such decisions are made. Our main results are as follows. We find evidence that taxes do not matter much. Financial planning for retirement consists of saving discretionary income instead of the required savings premium and choosing a secure type of investment which yields more than a savings book. Savers do not base their decisions on calculating and comparing rates of return or tax benefits. Instead, we find strong influences of relatively unqualified relatives, bank clerks and the desire for security. Thus, the financial outcome is strongly linked with the decision-making context and decision-making processes.
Keywords: D14; G23; H31; J32; 330; Financial Advice; Retirement Saving; Tax Incentives; Private Pension Plans; Peer Effects